Health systems decentralization and human resources management in low and middle income countries - Wang, Yan (2002)
The aim of this article is to explore the experiences of human resources management in the context of health sector decentralization. The initia review ofhealth sector decentralization covers issues relating to the context, content, formulation/implementation and impact of decentralization. The review of the literature on human resources management (HRM) and decentralization has identified a number of key points that are organized around the following HRM functions:HR planning/staff supply, personnel administration and employee relations, and performance management. The importance of the management of change is also highlighted. The article concludes by emphasizing the need to include human resources as a key issue in health systems change and emphasizes the areas of policy dialogue and research. - Reproduced.
Keywords: Decentralization; Human resources development; Health services